2019
DOI: 10.3390/su11236854
|View full text |Cite
|
Sign up to set email alerts
|

Key Drivers behind the Adoption of Electric Vehicle in Korea: An Analysis of the Revealed Preferences

Abstract: Electrification of passenger cars is one of the most popular ways to decarbonize the transportation sector and to reduce local air pollutants. Many researches have tried to examine what will be the driving factors to achieve the widespread adoption of electric vehicles (EVs). In this study, we analyzed the factors for EV adoption with the data of revealed preference from 2013 to 2017 in Korea. Analyses showed that the driving range of EVs and financial incentives have a positive impact on EV deployment. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Korean EV sales grew by 37% from January-May 2019 over the same period in 2018, while their EV exports surged in late 2018 as the Hyundai Kona Electric hit international markets (Argus Media 2019; Kane 2020). Statistical analysis of EV sales in Korea finds a correlation between longer vehicle range and increased EV market penetration, while it finds that fuel economy improvements from one EV to another do not increase consumer purchases (Kim and Heo 2019).…”
Section: South Koreamentioning
confidence: 98%
“…Korean EV sales grew by 37% from January-May 2019 over the same period in 2018, while their EV exports surged in late 2018 as the Hyundai Kona Electric hit international markets (Argus Media 2019; Kane 2020). Statistical analysis of EV sales in Korea finds a correlation between longer vehicle range and increased EV market penetration, while it finds that fuel economy improvements from one EV to another do not increase consumer purchases (Kim and Heo 2019).…”
Section: South Koreamentioning
confidence: 98%
“…The Spanish, Dutch and Austrians believe that altering the purchasing cost will be influential instrument to tilt purchasing decision. Similarly in South Korea, purchase subsidy and tax exemption are important motivational factors for green vehicle purchase behavior as the cost of having green vehicles is nearly double the cost of ICE, without the subsidy (Kim & Heo, 2019). While in Spain, Cordera et al (2019) found that the reduction in EV's purchase price resulted in an increase of the market share.…”
Section: Financial Attributesmentioning
confidence: 99%
“…Recently, governments have promoted BEVs by designing investment programs, legislation pieces and taxation policies [1][2][3][4][5][6][7][8], while manufacturers have innovated battery technology to improve performance and also reduce the range anxiety that relates to the poor adoption of BEVs [9][10][11][12][13]. The design of programs and policies alongside the innovation in battery technology are expected to jolt the system and stimulate a future rapid BEV growth, as reflected in demand assessments predicting reasonable market shares by 2020 [1,14,15] and conspicuous market shares by 2030-2050 [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%